2001
DOI: 10.1002/1522-2675(20010613)84:6<1821::aid-hlca1821>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

On the Solution Structure of PHB: Preparation and NMR Analysis of Isotopically Labeled Oligo[(R)-3-hydroxybutanoic Acids] (OHBs)

Abstract: Dedicated to Professor Edgar Heilbronner with best wishes on the occasion of his 80th birthdayWhile the chain conformation of poly-and oligo[(R)-3-hydroxybutanoate] (PHB, OHB) is known to be 2 1 -and 3 1 -helical in stretched fibers and in the crystalline state, respectively (Fig. 2), the structure in solution is unknown. To be able to determine the NMR-solution structure, specifically labeled linear oligomers have been prepared: a 16-mer consisting of alternating pairs of fully 13 C-labeled and non-labeled re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The development of design strategies for the construction of easily variable active sites at the inner surface of transmembrane pores is the first step toward such organic chemistry within confined anisotropic space. In sharp contrast to breathtaking progress being made with biotechnologically modified natural pores (1), reliable and general design strategies for synthetic ion channels and pores with easily variable internal active sites do not exist (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Reasonably straightforward covalent synthesis of barrel-like macromolecules with the required Ϸ3.5-nm height and variably functionalizable interior of Ն1.0 nm diameter is not (yet) possible.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The development of design strategies for the construction of easily variable active sites at the inner surface of transmembrane pores is the first step toward such organic chemistry within confined anisotropic space. In sharp contrast to breathtaking progress being made with biotechnologically modified natural pores (1), reliable and general design strategies for synthetic ion channels and pores with easily variable internal active sites do not exist (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Reasonably straightforward covalent synthesis of barrel-like macromolecules with the required Ϸ3.5-nm height and variably functionalizable interior of Ն1.0 nm diameter is not (yet) possible.…”
supporting
confidence: 90%
“…Reasonably straightforward covalent synthesis of barrel-like macromolecules with the required Ϸ3.5-nm height and variably functionalizable interior of Ն1.0 nm diameter is not (yet) possible. The more straightforward noncovalent syntheses (16)(17)(18)(19)(20) applied to barrellike supramolecules with ion channel activity is, with one possible exception (15), limited by apparent difficulties to position functional groups at internal concave surfaces (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, we have recently found that this trend toward ''peripheral crowding'' in supramolecular synthesis (16)(17)(18)(19)(20) can be bypassed in artificial ␤-barrels with p-octiphenyl ''staves'' and have used their rationally designed hydrophobic, ionophoric, and cationic interior to encapsulate guests with complementary characteristics in water and bilayer membranes (21,22).…”
mentioning
confidence: 55%
“…Moreover, polyesters such as PHB, in contrast to polyamides and polypeptides, have highly flexible backbone structures, since they lack the stabilizing element of internal hydrogen bonds and the rigidity of a peptide bond. The extremely high flexibility of the PHB backbone at physiological temperatures has been amply demonstrated by Seebach et al , using circular dichroism and fluorescence (FRET) measurements [31], nuclear magnetic resonance (NMR) spectroscopy [32,33] and molecular dynamics simulations [34]. However, it is important to note that the glass temperature of PHB is ~10 °C, so that the PHB backbone becomes increasingly more rigid as temperatures are lowered below the physiological range.…”
Section: Physical Properties Of Phbmentioning
confidence: 99%
“…± investigations on the structure of PHB in solution were undertaken. Although there are hints for the presence of folded secondary structures on the very short time scale of UV/ VIS spectroscopy (provided by FRET (Fluorescence Resonance Energy Transfer) [7] and CD [8] [9] measurements), no predominant secondary structure has been discovered on the longer NMR time scale 4 ). The conclusion was that PHB possesses a highly flexible backbone.…”
mentioning
confidence: 99%